Voting from abroad: Assessing the impact of local turnout on migrants' voting behavior - Divya Dev; Rubén Poblete-Cazenave; Alessandro Toppeta (Tinbergen Institute, 2021)
Over 150 countries allow expatriate citizens to vote in their country of origin. Yet, little is known about their voting behavior and how this is affected by host countries. Using unique micro-data on Chilean expatriates living in Europe, we study how the host country's turnout affects expatriates' electoral participation in the 2017 Chilean Presidential election. We focus on the 2014 European Parliament election turnout in the district of the Chilean's geocoded residence and exploit local transitory shocks to the cost of voting given by the rainfall on the day of the election. We find that migrants living in areas with higher political participation have lower engagement with their home country politics. A 1 percentage point increase in the host country's turnout decreases the electoral participation of Chilean expatriates by nearly 1 percentage point. The effects are stronger for young Chileans and those living in small communities, and in localities more welcoming to migrants. This suggests that integration into their local environment seems to play an important role on shaping political preferences.
Keywords: D72; F22; J15; P48; Z13; 330; Migration; Elections; Voting; Turnout; Expatriates; Rainfall